Disparity in the Burden of Caring for Older Persons between Families Living in Housing Estates and Traditional Communities in Thailand - Nadila Mulati; Myo Nyein Aung; Saiyud Moolphate; Thin Nyein Nyein Aung; Yuka Koyanagi; Siripen Supakankunti; Motoyuki Yuasa (MDPI AG, 2024)
Thailand's rapid population aging and reliance on family-based long-term care requires research into disparities in family caregiver burden. Since the type of residence matters to the caregiving outcome, this research aimed to examine the difference in caregiver burden between residents of private housing estates and traditional village communities. This cross-sectional study was conducted with 1276 family caregivers of community-dwelling Thai older adults, in Chiang Mai province, Thailand. The caregiver burden was examined using the Caregiver Burden Inventory (CBI), and the care recipients' dependency status was examined using Barthel's Activity of Daily Living (ADL). Descriptive analysis, multivariate analysis of variance test, and multiple logistic regression analysis were performed. Family caregivers living in a traditional village community were 1.607 times more likely to experience emotional burden (adj. OR 1.607, 95% CI: 1.049, 2.462) and 2.743 times more likely to experience overall caregiver burden (adj. OR: 1.163, 95% CI: 1.163, 6.471) compared to those in the private housing estate group. Our findings showed significant differences in caregiver burden based on residential area, contributing with insights to evidence-based policies, interventions, and programs to minimize disparities and promote family caregivers' health and well-being.